Fostering Environmental Awareness in Elementary Students Through the 'CILUKBA' Science Learning Program - Wulandari, Tri; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Heru (Jurnal Pendidikan MIPA, 2024)
Current educational developments require integration between academic learning and student character formation. One of the characteristics related to global issues is love of the environment, which can be instilled from an early age through a practical activity-based approach. The CILUKBA (Environmental Love Makes Us Happy) program is an initiative to teach the values of environmental love through science learning. This research aims to evaluate the success of the "CILUKBA" program in building environmentally caring character in grade 6 students at SD Negeri 3 Glodogan. This research uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and documentation. The research subjects involved 23 students, consisting of 10 male students and 13 female students. The research results show that the "CILUKBA" program has succeeded in increasing students' awareness of the importance of protecting the environment, demonstrated through activities of planting plants, managing plastic waste, and practicing environmentally friendly habits. In addition, students actively demonstrate sustainable environmental love behavior in their daily activities. In conclusion, the "CILUKBA" program is effective as a character-based science learning strategy to foster the value of love for the environment in elementary school students.        Keywords: character education, love of the environment, natural sciences, CILUKBA.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1593-1603